2012
DOI: 10.1590/s0100-736x2012000900007
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' perception about parasitic otitis in Gyr breed from three states of Brazil

Abstract: Pesq. Vet. Bras. 32(9) This study aimed to know the perception of Gir cattle breeders and farm employees about parasitic otitis and practices regarding methods of treatment and control. A questionnaire was applied on speciϐic topics about the disease. The results showed that the otitis occurred in 25 (89.3%) of the 28 farms studied, where the main etiologic agents were the nematodes Rhabditis spp. The majority of the farmers regarded the disease as a serious problem, mainly in cattle older than eight years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 6 publications
1
4
0
9
Order By: Relevance
“…No Brasil, Leite et al (19) relataram que 89,3% (25/28) das fazendas criadoras de animais Gir reportavam a presença de otite parasitária causada por Rhabditis spp. e que 74,1% dos proprietários classificaram como grave o problema.…”
Section: Desenvolvimento Do Assuntounclassified
See 2 more Smart Citations
“…No Brasil, Leite et al (19) relataram que 89,3% (25/28) das fazendas criadoras de animais Gir reportavam a presença de otite parasitária causada por Rhabditis spp. e que 74,1% dos proprietários classificaram como grave o problema.…”
Section: Desenvolvimento Do Assuntounclassified
“…Os nematoides do gênero Rhabditis, família Rhabditidae, são responsáveis pela otite parasitária em bovinos (8). A doença foi relatada em países de clima quente e úmido, como Colômbia (20), Tanzânia (21), Quênia (22), apesar da maioria dos relatos serem do Brasil, nas regiões Norte, Nordeste, Sudeste e Centro-Oeste, com uma prevalência de 52,2 -100% (4,8,19). As espécies descritas nesse gênero incluem, Rhabditis freitasi, Rhabditis costai, Rhabditis insectivora, Rhabditis terrestres, Rhabditis blumi (1,23).…”
Section: Aspectos Etiológicos E Epidemiológicosunclassified
See 1 more Smart Citation
“…The known resistance of the zebu breeds to endoparasites and ectoparasites also occurs in Gir animals (Gasparin, 2007); however, it has been observed that the Gir cattle is highly susceptible to a parasitic disease caused by rhabditiform nematodes that develops in the auditory canal and predisposes animals to external otitis. This parasitic disease causes mild to very severe clinical symptoms, especially in adults, which have abundant ear secretion, inflammation and local pain (Leite et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although parasitic otitis caused by rhabditiform nematodes in Gir cattle has been known in Brazil for more than forty years, therapeutic measures commonly performed to control it are generally ineffective (Martins Jr. et al, 1971;Leite et al, 2012). A preventive program of parasitic otitis has not been established because some important aspects of the diseases such as its epidemiology, the parasites' biological cycle and the nematodes' transmission mechanisms had not been well understood yet.…”
Section: Introductionmentioning
confidence: 99%